2021
DOI: 10.21162/pakjas/21.801
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic analysis of ecotourism activities of women in Turkey

Abstract: Ecotourism is a type of tourism in which maximum benefits are provided to local people while protecting the environment. Local people care more about the sustainability of biodiversity and they are very effective at protecting it. Kure Mountains National Park is one of the most important protected areas for accelerating ecotourism, having tremendous natural resources, protected traditional cultures, caves, canyons, waterfalls and natural wonders. In this study, we aimed to examine the support of women in ecoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The distribution of workers based on job titles revealed operatives represented the highest proportion, 66.73% as typical in the seafood processing sector. Similarly, previous studies conducted by Duyar and Bayraklı (2005), Çapkın et al (2008), Çağlak et al (2012), andAltunel, (2021) reported high numbers of operatives. The cumulative percentage of workers in regard to job satisfaction was up to 85.33% including satisfied and tolerable answers, only 4.89% were not satisfied.…”
Section: Discussionsupporting
confidence: 69%
“…The distribution of workers based on job titles revealed operatives represented the highest proportion, 66.73% as typical in the seafood processing sector. Similarly, previous studies conducted by Duyar and Bayraklı (2005), Çapkın et al (2008), Çağlak et al (2012), andAltunel, (2021) reported high numbers of operatives. The cumulative percentage of workers in regard to job satisfaction was up to 85.33% including satisfied and tolerable answers, only 4.89% were not satisfied.…”
Section: Discussionsupporting
confidence: 69%
“…A few articles included in the present section have potential implications for the residents of national and natural parks and people living in their vicinity. Altunel [145] addressed a subject of potential sensitivity in some cultures-the involvement of local women in ecotourism activities. Other authors analysed the local people's attitude towards sustainable ecotourism development in parks [151] and their engagement in participatory opportunities [177].…”
Section: Description Of Research Papers Focusing On Local Communities...mentioning
confidence: 99%